In Vivo Determination of Mitochondrial Function Using Luciferase‐Expressing Caenorhabditis elegans: Contribution of Oxidative Phosphorylation, Glycolysis, and Fatty Acid Oxidation to Toxicant‐Induced Dysfunction. Issue 1 (1st August 2016) - Luz, Anthony L.; Lagido, Cristina; Hirschey, Matthew D.; Meyer, Joel N.
Abstract: Mitochondria are a target of many drugs and environmental toxicants; however, how toxicant‐induced mitochondrial dysfunction contributes to the progression of human disease remains poorly understood. To address this issue, in vivo assays capable of rapidly assessing mitochondrial function need to be developed. Here, using the model organism Caenorhabditis elegans, we describe how to rapidly assess the in vivo role of the electron transport chain, glycolysis, or fatty acid oxidation in energy metabolism following toxicant exposure, using a luciferase‐expressing ATP reporter strain. Alterations in mitochondrial function subsequent to toxicant exposure are detected by depleting steady‐state ATP levels with inhibitors of the mitochondrial electron transport chain, glycolysis, or fatty acid oxidation. Differential changes in ATP following short‐term inhibitor exposure indicate toxicant‐induced alterations at the site of inhibition. Because a microplate reader is the only major piece of equipment required, this is a highly accessible method for studying toxicant‐induced mitochondrial dysfunction in vivo. © 2016 by John Wiley & Sons, Inc.